Generation Z: Financial Literacy, Sharia Financial Literacy, Attitude, and Behavior - Heni Rahmani Putri; Muhsin N. Bailusy; Hartaty Hadady (AIBPM Publisher, 2021)
This study aims to investigate the influence of financial literacy and Sharia financial literacy on financial attitude and behavior. The population in the study were students of Khairun University and IAIN Ternate. A total of 188 respondents were involved and purposively selected as the samples. The study used validity and reliability tests as part of the instrument test. For hypothesis testing, a simple regression analysis was used. The results showed that all hypotheses were supported. The final part of the study discusses findings, conclusions, and suggestions for future research.